Relationship between erythropoietin and hepcidin among transfused Malaysian adult thalassemic patients - Ibraheem, Shahad Mohammed (2022)
Thalassemia is a genetic blood disorder characterized by insufficient hemoglobin level or due to mutation in the globin chains causing an anemic condition with iron overload despite no history of transfusion; thus, insufficient hemoglobin will cause an imbalance of erythropoietin (an endogenously produced hormone used to maintain the oxygen levels in the blood carried out by hemoglobin molecule) and hepcidin (a peptide hormone responsible for body iron regulation). Besides, many thalassemic patients require a recurrent blood transfusion to survive alongside the different chelation therapy that both remarkably affect these biomarkers. The study was embarked to identify the relationship of serum erythropoietin and human hepcidin in differently transfused thalassemia patients. A cross-sectional study designed for 150 respondents matched by gender; 75 thalassemic patients recruited from Thalassemia Clinic of Ampang Hospital plus 75 healthy participants from FPSK, UPM. The required data which included variables such as body mass index (BMI); hemoglobin (Hb); serum ferritin (SF); liver iron concentration (LIC) and cardiac T2*, gathered using proforma and medical records, except for serum erythropoietin (EPO) and hepcidin (HEPC) assessed using enzyme-linked immunosorbent assay (ELISA kit) from Aug 2020-Oct 2020. HEPC levels correlated inversely with EPO in both MTG (r = -0.618, P < 0.00001) and NMTG (r = -0.8243, P=0.000048). In contrast, HEPC correlated positively with SF (MTG: r = 0.7833, P < 0.00001 and NMTG: r =0.8587, P=0.000011) and LIC (MTG: r = 0.4348, P= 0.000648 and NMTG: r =0.8817, P < 0.00001). Similarly, there was a positive relationship between BMI and Hb (MTG: r = 0.2604, P= 0.0487* and NMTG: r =0.4898, P=0.0463). Most of the thalassemia patients experienced iron overload, had higher levels of EPO, HEPC, SF and LIC when compared to patients with non-iron overload with a p-value of (0.027458, 0.000339, 0.026304 and 0.005644), respectively. The current study showed a significant inverse relationship between serum erythropoietin and human hepcidin in thalassemia patients compared to the healthy population. Thalassemia patients with low Hb seemed to have underweight BMI classification due to the positive relationship between BMI and Hb. The main variables (Hb, EPO, HEPC, SF, LIC and Cardiac T2*) were more likely to be associated with the phenotypes of thalassemia rather than multi-genes (α and β-globin chains); also, the multiple blood transfusion and the different chelation therapies efficiently affected the values and association of those variables, HEPC specifically. Besides the iron overload that almost all thalassemia patients had, a specific group of those iron overload patients developed pertaining complications to iron overload.